Breeding for the improvement of indigenous chickens of Bangladesh: performance of foundation stock - Faruque, Shakila; Bhuiyan, AKFH; Ali, Md Yousuf; Joy, Ziaul Faruque (Asian Journal of Medical and Biological Research, 2017)
Selection is one of the vital tools for improving the indigenous chicken genetic resources. A total of 1585-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched for this study to form foundation stock. Improvement target of egg weight was to increase by 1g and improvement target of egg production rate was to increase by 2 % per generation. In foundation stock, selection was practiced at 40-week of age, on the basis of an index comprising the parameters of age at first egg (ASM), body weight(BW), egg production(EP) and egg weight(EW). Data were analyzed in CRD by General Linear Model (GLM) Univariate Procedure. Significantly highest fertility (82.71%) and hatchability (82.20%) were found in ND genotype. Significantly (P<0.001) highest body weight of day-old chicks and daily weight gain was found in H genotype than other two genotypes. There was a non-significant (P>0.05) variation in FCR among the native chicken genotypes. NN genotype (3.46%) had non-significantly (?2 = 3.62; P > 0.05) higher chick mortality than ND (1.63%) and H (2.11%) at brooding period (0-4 weeks). Significantly (P<0.01) higher dressing percentage was found in NN (64.58) genotype than ND (60.26) and H (61.70) genotypes. Non-significantly higher egg production in selected group was found in H (70) genotype than ND (68) and NN (67) genotypes. Significantly (P<0.001) highest shape index and Haugh unit were found in H and ND genotypes, respectively. As a result of selection, egg production is expected to improve by 0.562, 0.932 and 0.755%, respectively for ND, H and NN genotypes. In terms of reproductive traits ND was superior, in terms of productive traits H genotype was superior and in terms of dressing percentage and breaking strength NN genotype was superior. These findings of the study also give an impetus for continuing the research for more generations to fulfill the objectives of the long-term programme. Asian J. Med. Biol. Res. March 2017, 3(1): 80-87